The role of autophagy-related proteins in the pathogenesis of neuromyelitis optica spectrum disorders. Issue 6 (1st June 2022) - Guo, Hong-Liang; Shen, Xiao-Ran; Liang, Xiao-Ting; Li, Ling-Zhou
ABSTRACT: This study aimed to investigate the expression of autophagy-related proteins in a mouse model of neuromyelitis optica (NMO). Mice were assigned to one of four groups: an animal experimental model group (NMO-EAE group, given with exogenous IL-17A), Interleukin-17 monoclonal antibody intervention group (NMO-EAE_0IL17inb), No exogenous interleukin-17 enhanced immune intervention group (NMO-EAE_0IL17), and a control group. Behavioral scores were assessed in each group, and the protein expressions of sequestosome 1 (P62), Beclin-1, the mammalian target of rapamycin (mTOR), phosphoinositide 3-kinase (PI3K-I), and LC3II/LC3I were detected using Western blotting. In the NMO-EAE_0IL17 group, the expression of Beclin-1 decreased, the LC3II/LC3I ratio was lower, and the expressions of P62, mTOR, and PI3K-I increased; after administration of IL-17A inhibitor into the brain tissue, however, the expression of Beclin-1 increased significantly, along with the LC3II/LC3I ratio, while the expressions of P62, mTOR and PI3K-I protein decreased significantly. In terms of behavioral scores, the scores of optic neuritis and myelitis were more serious, onset occurred earlier and the progress was faster, after the administration of IL-17A. In the mechanism of NMO animal model, IL-17A may regulate autophagy and affect the disease process through the activation of the PI3K–mTOR signaling pathway. GRAPHICAL ABSTRACT: uf0001